2013
DOI: 10.1158/0008-5472.sabcs13-p6-06-13
|View full text |Cite
|
Sign up to set email alerts
|

Abstract P6-06-13: Optimized prediction of clinical outcome by the PREDICT plus tool and the 70-gene signature in early stage node-negative breast cancer

Abstract: Background Established breast cancer guidelines and online tools use clinico-pathological factors including age, tumor size and grade to evaluate the risk of recurrence and select patients who are eligible to receive adjuvant chemotherapy (ACT). One of the online tools, PREDICT plus, was recently updated and is the first tool to include HER2 status and method of detection in risk assessment. Another tool to better guide AST decisions is the 70-gene signature. The 70-gene signature is a gene-expression classifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A recent study has reported that the Oncot ype DX® RS is an independent prognostic factor in ER-negative, HER2-negative tumours but the improvement in discrimination from the RS compared to clinical variables was less than the improvement obtained from the improvement obtained by IHC4, an immunohistochemistry test that includes KI67 [ 20 ]. Another recent study explored the addition of the 70-gene signature (MammaPrint™) to Predict (v2) in 427 patients with early stage breast cancer and found no significant improvement in 5- or 10-year survival predictions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that the Oncot ype DX® RS is an independent prognostic factor in ER-negative, HER2-negative tumours but the improvement in discrimination from the RS compared to clinical variables was less than the improvement obtained from the improvement obtained by IHC4, an immunohistochemistry test that includes KI67 [ 20 ]. Another recent study explored the addition of the 70-gene signature (MammaPrint™) to Predict (v2) in 427 patients with early stage breast cancer and found no significant improvement in 5- or 10-year survival predictions [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has reported that the Oncotype DX® RS is an independent prognostic factor in ER-negative, HER2-negative tumours but the improvement in discrimination from the RS compared to clinical variables was less than the improvement obtained from the improvement obtained by IHC4, an immunohistochemistry test that includes KI67 [20]. Another recent study explored the addition of the 70-gene signature (MammaPrint™) to Predict (v2) in 427 patients with early stage breast cancer and found no significant improvement in 5-or 10-year survival predictions [21].…”
Section: Discussionmentioning
confidence: 99%